1978
DOI: 10.1159/000123783
|View full text |Cite
|
Sign up to set email alerts
|

Threat, Attack and Flight Elicited by Electrical Stimulation of the Ventromedial Hypothalamus of the Marmoset Monkey <i>Callithrix jacchus</i>; pp. 276–293

Abstract: In order to elucidate whether relatively primitive primates show a similar topological organization of substrates mediating defense and flight within the ventromedial hypothalamus as has been found in other mammals, 15 marmosets (Callithrix jacchus) were chronically implanted with a total of 57 electrodes for electrical stimulation. Experiments took place in a familiar environment and under systematically altered conditions. All anatomical sites yielding vocal threat and short attacks were found to be situated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…We chose the VMHdm for our studies because it is an evolutionarily conserved brain structure (Kurrasch et al, 2007) that receives monosynaptic inputs from predator-responsive regions of the medial amygdala (Choi et al, 2005;Bergan et al, 2014;Kunwar et al, 2015) and provides monosynaptic outputs to the dPAG, a brainstem structure that is required for defensive responses to predators (Dielenberg et al, 2004;Aguiar & Guimarães, 2009). Previous work has demonstrated that electrical stimulation of the VMHdm elicits panic attacks in humans (Wilent et al, 2010) and escape behaviour in non-human primates (Lipp & Hunsperger, 1978), arguing for a critical role in the production of emotional responses. Pharmacogenetic inhibition of the VMHdm in mice suppresses predator fear behaviour (Silva et al, 2013), and optogenetic stimulation elicits flight, immobility, and avoidance (Lin et al, 2011;Falkner et al, 2014;Kunwar et al, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the VMHdm for our studies because it is an evolutionarily conserved brain structure (Kurrasch et al, 2007) that receives monosynaptic inputs from predator-responsive regions of the medial amygdala (Choi et al, 2005;Bergan et al, 2014;Kunwar et al, 2015) and provides monosynaptic outputs to the dPAG, a brainstem structure that is required for defensive responses to predators (Dielenberg et al, 2004;Aguiar & Guimarães, 2009). Previous work has demonstrated that electrical stimulation of the VMHdm elicits panic attacks in humans (Wilent et al, 2010) and escape behaviour in non-human primates (Lipp & Hunsperger, 1978), arguing for a critical role in the production of emotional responses. Pharmacogenetic inhibition of the VMHdm in mice suppresses predator fear behaviour (Silva et al, 2013), and optogenetic stimulation elicits flight, immobility, and avoidance (Lin et al, 2011;Falkner et al, 2014;Kunwar et al, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it remains unclear whether neural activity in the medial hypothalamus is sufficient for the encoding of fear. Stimulation of the VMHdm is sufficient to elicit flight behaviour in many species, incluing rodents, cats, and monkeys (Hess & Br€ ugger, 1943;Brown et al, 1969;Lipp & Hunsperger, 1978;Lin et al, 2011;Kunwar et al, 2015;Wang et al, 2015), and panic attacks in humans (Wilent et al, 2010), and pharmacological activation of the PMD or optogenetic activation of the VMHdm is sufficient to serve as an unconditioned stimulus for contextual fear conditioning (Pavesi et al, 2011;Kunwar et al, 2015). However, these responses might simply reflect acute activation of the motor circuits associated with predator fear, and leave it unclear whether neural activity in the medial hypothalamus might encode an internal emotional state (Anderson & Adolphs, 2014) independently of its behavioural outputs.…”
Section: Introductionmentioning
confidence: 99%
“…What brain mechanisms control appetitive aggression reward? Seminal work on unconditioned (innate) aggression identified the hypothalamus as a critical brain region underlying aggressive behavior in cats (Glusman & Roizin 1960;Macdonnell & Flynn 1964), rats (Bandler 1969) and non-human primates (Lipp & Hunsperger 1978). Collectively, the midbrain hypothalamic brain regions contributing to aggression have been termed the hypothalamic attack area (HAA), spanning from the mediobasal hypothalamus to the lateral ventromedial nucleus (VMH) (Toth et al 2010).…”
Section: Appetitive Aggression Reward In Rodentsmentioning
confidence: 99%
“…Hypothalamic conditioning resulted in stereotyped efl"ects dominated by facilitation of jaw closers and inhibition of jaw openers. Their assumption that mental stress afl"ects the hypothalamic agonistic centres is supported by the observations in monkeys of Lipp (1978) and Lipp & Hunsberger (1978).…”
Section: Discussionmentioning
confidence: 91%